COVID-19 and the collapse of global trade: building an effective public health response. Issue 2 (February 2021) - Barlow, Pepita; van Schalkwyk, May CI; McKee, Martin; Labonté, Ron; Stuckler, David
Summary: The scale of the COVID-19 pandemic is a consequence of international trade and globalisation, with the virus spreading along established trade and travel routes. However, the pandemic also affects international trade through reductions in both supply and demand. In this Viewpoint we describe the many implications for health and propose ways to mitigate them. Problems include reduced access to medical supplies (in particular, personal protective equipment and tests), budgetary shortfalls as a result of reduced tariffs and taxes, and a general decline in economic activity—leading, in many cases, to recessions, threats to social safety nets, and to increased precariousness of income, employment, and food security. However, in exceptional cases, the pandemic has also brought some transient benefits, including to the environment. Looking ahead, there will be great pressure to further liberalise rules on trade to encourage economic recovery, but it is essential that trade policy be informed by its many consequences for health to ensure that the benefits are maximised and threats are minimised through active identification and mitigation.